Rupture of the Superior Sagittal Sinus in Penetrating Head Injury—Management of a Rare Trauma Mechanism - Schlag, Holger; Neuhoff, Jonathan; Castein, Jens; Hoffmann, Christoph; Kandziora, Frank (Journal of Neurological Surgery Reports, 2022)
Civilian penetrating head injury caused by foreign objects is rare in Germany (Europe), but can result in complex neurovascular damage. We report on a patient who in suicidal intent inflicted on himself a penetrating brain injury near the vertex with a captive bolt gun. A laceration at the junction of the middle to the posterior third of the superior sinus occurred by bolt and bone fragments leading to critical stenosis and subsequent thrombosis. Upon surgery, the proximal and distal sinus openings were completely thrombosed. The sinus laceration was closed by suture and the intraparenchymal bone fragments were retrieved. Postoperative angiography disclosed persistent occlusion of the superior sagittal sinus. The patient did not develop any symptoms due to venous congestion (edema, hemorrhage), suggesting sufficient collateral venous outflow. The patient completely recovered despite the complexity of the lesion.
Keywords: penetrating head injury; superior sagittal sinus; penetrating brain injury; fractures